PEMANFAATAN LAHAN PEKARANGAN UNTUK TANAMAN OBAT KELUARGA (TOGA) PADA MASA PANDEMI COVID-19 DI BANJAR TANJUNG DESA SANUR KAUH - Putu Lakustini Cahyaningrum; I Kadek Indra Wiguna (UNHI Press, 2021)
This service activity is carried out at Br Tanjung, Sanur Kauh Village, South Denpasar District. The use of vacant or narrow land in the yard of the house, especially in Br Tanjung is still not optimally carried out by the local community for family medicinal plants (TOGA). The target of this service is PKK Br Tanjung women who are affected by the covid 19 pandemic. The purpose of this activity is to increase knowledge and understanding in the management of family medicinal plants (TOGA), so that people know the types and benefits of medicinal plants that can be used in increasing the added value of herbal medicinal plants in the yard of the house to be useful in increasing the body's immunity during the covid-19 pandemic. The method used is the active participation method which is divided into 3 stages, namely through the process of socializing and counseling the benefits of family medicinal plants (TOGA), planting family medicinal plants and evaluating activities. From the results of the service, it is found that a narrow and empty yard can be planted with family medicinal plants (TOGA), especially by PKK women. In addition, PKK Br Tanjung, Sanur Kauh Village through this activity received positive added value and could increase their knowledge and skills about types and techniques of medicinal plant cultivation so as to encourage their interest in using narrow yards for medicinal plant cultivation, especially during the covid pandemic. -19 which requires every citizen to maintain health in a natural way.